1977
DOI: 10.1002/jsfa.2740280605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen and phosphorus fertilisers on yield and on inorganic and organic composition of italian ryegrass grown on phosphorus‐deficient soil

Abstract: Italian ryegrass (Lolium rnultiflorum) S22, grown in a greenhouse in phosphorusdeficient soil in pots was given 40 and 160 mg N/kg of soil (as ammonium nitrate) and 5, 25 and 100mgP/kg of soil (as calcium tetrahydrogen diorthophosphate). Giving more nitrogen increased yields only when adequate phosphorus was applied. A significant response to added phosphorus was obtained when ryegrass dry matter contained about 0.15 % P or less. Nitrogen increased the amount of sugars but decreased that of fructosan. Phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…About 20-30% of the nitrogen content in fresh forages is in the form of non-protein N (NPN) (Mangan 1982), represented by nitrates, free amino acids, peptides and secondary metabolites. Fertilisation with N will increase N concentration in the DM of forage, but the increase will be greater if N is not the first limiting nutrient for plant growth (Nowakowski & Byers 1972;Nowakowski et al 1977). In addition to the increase in total N, nitrogenous fertiliser usually increases the proportion of NPN in the forage (up to 45% of the total N: Table 3) and this can affect nutrition, production and health of the animal.…”
Section: Forage Responses To Additional N: Nutritional and Health Imp...mentioning
confidence: 99%
“…About 20-30% of the nitrogen content in fresh forages is in the form of non-protein N (NPN) (Mangan 1982), represented by nitrates, free amino acids, peptides and secondary metabolites. Fertilisation with N will increase N concentration in the DM of forage, but the increase will be greater if N is not the first limiting nutrient for plant growth (Nowakowski & Byers 1972;Nowakowski et al 1977). In addition to the increase in total N, nitrogenous fertiliser usually increases the proportion of NPN in the forage (up to 45% of the total N: Table 3) and this can affect nutrition, production and health of the animal.…”
Section: Forage Responses To Additional N: Nutritional and Health Imp...mentioning
confidence: 99%
“…Interactions of Nand P fertiliser have been demonstrated (Dev 1964, Lambert & Toussaint 1977, Nowakowski et al 1977, Soon & Miller 1977. However, these relate to combined applications of N and P, and the interaction is attributable to the influence of N fertiliser on P availability through changes in soil chemistry and/or plant physiology (Cope & Hunter 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Significant positive relationships between soil P and Lolium cover for both the PFLA plots and the CS Improved Grassland plots (where the relationship was unimodal) indicated that some of the PFLA member farms may retain characteristics of conventional systems, perhaps reflecting a recent transition and legacy effects on existing swards and soils or, in some cases, continued management with P fertilizers. The relationship reflects positive (and agriculturally desirable) impacts of soil P on Lolium growth established decades ago (Nowakowski et al., 1977). Despite similarities in these relationships, Lolium cover was significantly lower in PFLA grassland than in CS Improved Grassland.…”
Section: Discussionmentioning
confidence: 96%